the new silk road - Константин Лидин (Проект Байкал, 2022)
Thousands of years ago, a system of routes was taking shape across the Eurasian continent, transporting people, goods, ideas and technology from east to west and from west to east. The armies of Alexander the Great and Genghis Khan passed along those routes; caravans of merchants carried silk, porcelain, spices and wisdom books. Today the concept of the Great Silk Road is not just coming to life, but is becoming one of the large-scale ideas for the development of dozens of states, up to the global level. The New Silk Road will be implemented simultaneously along many parallel paths. The southern ones will pass across the territories of Central Asia, Iran and Turkey. The northern routes will mainly run through Russia, including its Arctic territorial waters. These large-scale linear projects represent a major challenge and, at the same time, a tremendous development opportunity for many decades (centuries?) ahead. We start to discuss the New Silk Road by selecting materials on some specific aspects of the project and look forward to discussing it further – as its global nature demands.